Rapid phase-controlled microwave synthesis of nanostructured hierarchical tetragonal and cubic beta-In2S3 dandelion flowers - Naik, S. D.; Jagadale, Tushar C.; Apte, S. K.; Sonawane, S.; Kulkarni, M. V.; Patil, S. I.; Ogale, Satishchandra B.; Kale, B. B. (Chemical Physics Letters, 2008)
Phase controlled synthesis of hierarchical nanostructured beta-In2S3 dandelion flowers is realized by a rapid microwave solvothermal process using indium metal, nitric acid and thiourea as precursors. The tetragonal and cubic phases of the compound have been successfully and separately stabilized in the same type of dandelion morphology by using aqueous-mediated and methanol-mediated synthesis, respectively. The possible mechanism responsible for phase control is discussed. Optical properties of the flowers as well as their hydrogen generation capability by photodecomposition of H2S under visible light are also reported. (c) 2007 Elsevier B.V. All rights reserved.